(untitled) (Journal of Nepalese Business Studies, 2018)
The development of the mutual fund industry is the greatest investment success story of the twentieth century in United States and this industry also emerged as the most dynamic segment of the Indian financial system on that time. But the history of mutual fund in Nepal started only with the establishment of "NCM Mutual Fund 2050" in 1993. Currently there are ten mutual fund schemes listed and traded in Nepal Stock Exchange that provide investment opportunities for investors in mutual funds market. In this context, the purpose of this paper is to provide necessary facts and figures related to the mutual fund schemes in Nepal based on secondary data. The paper includes mutual fund companies, development mutual funds and review of empirical studies on mutual funds as preliminary discussion, and includes current mutual fund schemes; funds sizes, maturity periods, market price, net asset value and dividend income of mutual fund schemes on analytical section. The Journal of Nepalese Business Studies Vol. X No. 1 December 2017, Page: 85-95